The twisted Whittaker modules over the quantum group of type B2. Issue 1 (2nd January 2023) - Xia, Limeng; Wang, Shengyuan; Xu, Senrong
Abstract: Let g be the complex simple Lie algebra of type B 2 . In this paper, we give the explicit generators of the center of the quantum group U q ( g ) . We also study the twisted Whittaker modules over U q ( g ), and all nonsingular twisted Whittaker modules are classified.